PENINGKATAN PRODUKTIVITAS KOMUNITAS TULI-DENGAR DI RAYA HONEY SIBETAN BERBASIS SISTEM NYAMA BRAYA - Sumandya, I Wayan; Setiawan, Gde Iwan; Dharmadewi, A A Istri Mirah (Jurnal Abdi Insani, 2025)
The Great Honey Sibetan Deaf-Hearing Community is an inclusive community engaged in honey bee cultivation in Sibetan Village, Karangasem, Bali. This community faces challenges in honey productivity and harvesting technology, as well as limited access to training and mentoring. The Nyama Braya work system, as a local wisdom, has become a strength in building collaboration between deaf and hearing members. Technical and production capacity building remains an urgent need. This activity aims to increase community productivity through training, mentoring, and the application of STEM-based technology. This activity also encourages the replication of an empowerment model based on inclusion and local wisdom. The activity methods include program outreach, training on the installation of STEM-based Trigona bee boxes and harvesting tools, and ongoing mentoring and productivity evaluation. Results of the activity show an increase in the number of bee colonies from 40 to 75. Honey production increased from 30 liters to 54 liters per quarter, and all community members are able to operate modern harvesting equipment effectively. Participant reflections indicate increased self-confidence, collaboration, and social recognition from the surrounding community. This activity effectively increases productivity, independence, and community collaboration through the integration of the STEM approach and Nyama Braya values.